Knowledge, attitude and practice regarding measles vaccine campaign among medical and engineering students: Baghdad, 2011 - Akram*, Wijdan; khalaf, Yosrra; Marzook***, Ahmed A. (AL-Kindy College Medical Journal, 2015)
Background: The strategy for eliminating measles from Iraq includes conducting mass immunization campaign against measles, within the framework of the national strategic plan for the elimination of this disease. Awareness about this campaign is fundamental for their success.Objective: The study aims at finding out the knowledge, attitudes and practices regarding vaccination against measles among two groups of students in two different colleges ( medical and engineering) .To report uptake of Measles vaccine and reasons for declining the vaccine among medical and non-medical students in the campaignMethod: Across sectional study has been conducted at Al-Kindy College of Medicine/ Baghdad University and University of Technology for the period from first of December 2011 till fifteenth of April 2012. A convenience sample of 180 students of the first and second stage including (81 male, 99 female) students from Al- Kindy College of Medicine and 180 students (87 male, 93female) from University of Technology department of Mechanical Engineering. All students were given a questionnaire to assess their knowledge of the campaign and the vaccine.Results: Overall 55.8 % of medical and engineering students accepted the vaccine with higher uptake amongmales than females ( 58.9 % and 53.1% respectively). Almost 44.2 % of students who did not accept the vaccine gave their reason as having little information about the vaccine and said that the vaccine is ineffective.Conclusion: In spite of awareness of the effect of measles campaign among students of the Medical College in Baghdad University and University of Technology but the measles campaign in university students may have been more successful with better use of health education messages.